Exploring Children’s World through Tafsir: A Critical Examination of Abdul Mustaqim’s Tafsir Juz ‘Amma for Kids - Aes, Sururul; Ursa Agniya (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2024)
The Qur'an as a guide for Muslims will be easily understood if there is an interpretation. Basically in an interpretation there are several things that must be considered. First is the ease with which the interpretation is understood and second is the effectiveness of the interpretation. This study aims to analyze how effective Tafsir Juz ‘Amma For Kids is on children's understanding of the Qur'an at an early age. This research uses descriptive qualitative methods to explore the events observed and Content Analysis as the data analysis technique. The findings of this study are very important because it highlights the extensive influence on a child's understanding of the Qur'an starting from an early age, and highlights the effectiveness of the materials of this tafsir for the needs of early childhood in learning and understanding God's messages easily. The results of the study not only provide deep insight into the effectiveness of Tafsir Juz ‘Amma For Kids, but also provide an understanding of the similarities in the need for interpretation of the Qur'an, young or old, male or female, adults or children. In the context of the archipelago, especially Indonesia, this article highlights the great and real contribution of a Tafsir Juz ‘Amma For Kids in understanding the message of religion from an early age.